Subiektywność - obiektywność poznania. Refleksje metodologiczne w kontekście badania wzorów doświadczeń zawodowych absolwentów pedagogiki = Subjectivity - objectivity of cognition. Methodological afterthoughts in the context of research on the models of professional experiences of pedagogy graduates - Urbaniak-Zając, Danuta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article formulates a thesis that the meaning of "subjectivity" and "objectivity" is not obvious and it is difficult to preserve in empirical research their "ontological" understanding. The justification behind drawing attention to this - seemingly - obvious issue is still occurring (especially among people superficially familiar with quality methodology) conviction, that quantity research aspire to "objective cognition", unlike, quality research - aspires to the presentation of an individual, "subjective perspective" of human experiences.
Keywords: subiektywność; obiektywność; poznanie; kognitywistyka